Influence Of Good Corporate Governance, Capital Structure And Sales Growth On Firm Value - Dyah Ayu Tri Utami; Lyandra Aisyah Margie (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine and analyze the influence of Good Corporate Governance, capital structure, and sales growth on firm value in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Methodology: This research employs an associative quantitative approach using empirical panel data. The sample consists of 14 companies selected through purposive sampling, resulting in 70 firm-year observations. Data were analyzed using panel data regression with the assistance of EViews 12 software. Good Corporate Governance is proxied by independent commissioners and managerial ownership. Results: The results indicate that, simultaneously, independent commissioners, managerial ownership, capital structure, and sales growth influence firm value. Partially, managerial ownership has a significant effect on firm value, while independent commissioners, capital structure, and sales growth do not show a significant effect. Novelty: This study provides a comprehensive panel data analysis of governance and financial factors affecting firm value in the non-cyclical consumer sector. Findings: Managerial ownership emerges as a key governance mechanism in enhancing firm value compared to other governance and financial indicators. Originality: The originality of this study lies in its sector-specific focus and recent empirical data within the Indonesian capital market. Conclusions: Strengthening managerial ownership structures may be more effective in increasing firm value than relying solely on board composition or financial leverage. Type of Paper: Empirical Quantitative Research Paper.